ICEV Recycling in Environments with Limited Conventional Energy: Insights from a Queuing Model - Manuel Alberto M. Ferreira (Theory and Applications of Engineering Research Vol. 7, 2024)
Nowadays Sustainability is a huge issue. Sustainability deals with the need for the protection of the natural environment and ecosystems health and requires innovation and commitment with the future. This manuscript presents an economic supported decision process modelled through a M|G| \(∞\) queue system (M means that arrivals follow a Poisson process, G (general) that the service time can follow any probability distribution, and \(∞\) that there are infinite servers) to help to choose if either ICEV-Internal Combustion Engine Vehicles, normally cars but not only, turn idle when conventional energy becomes scarce, or a new status quo is required. In such a case, they are recycled, becoming either EV-Electric Vehicles or HEV-Hybrid Electric Vehicles or FCEV-Fuel Cell Electric Vehicles, or are dismantled (DV-Dismantled Vehicles). Our model shows that when the rhythm ICEV become EV, HEV, FCEV and DV is greater than the rate at which they get idle the system tends to balance. In a cost-benefit analysis perspective, there are minimum benefits above which, both dismantling and recycling, are interesting. Additionally, the most interesting is the one for which the minimum benefit is the least.